Как вы упростите \((p+q*omega+r*omega^2)/(r+p*omega+q*omega^2)\)?

0
0

Как вы упростите \((p+q*omega+r*omega^2)/(r+p*omega+q*omega^2)\)?

0
0

Смотрите объяснение …

Объяснение: \[omega = -1/2+sqrt(3)/2i\] является примитивным сложным кубическим корнем \[1\] ,
Так \[omega^3 = 1\] а также \[omega^4 = omega\] \[(p+q*omega+r*omega^2)/(r+p*omega+q*omega^2)\] \[=(p*omega^3+q*omega^4+r*omega^2)/(r+p*omega+q*omega^2)\] \[=(r*omega^2+p*omega^3+q*omega^4)/(r+p*omega+q*omega^2)\] \[=((cancel(((r+p*omega+q*omega^2))))omega^2)/(cancel(((r+p*omega+q*omega^2))))\] \[=omega^2\]

Показан 1 результат